KAJIAN TINGKAT KENYAMANAN VEGETASI BERDASARKAN KONDISI SUHU DAN KELEMBABAN UDARA PADA AREA RUANG TERBUKA HIJAU. Studi Kasus Pada Area RTH Taman Nostalgia dan RTH Jalan Piet A. Tallo, Kota Kupang, Provinsi Nusa Tenggara Timur - Putra, Bukhari Muslim Maloko; Purnama, Maria M. E.; Riwu Kaho, Norman P.L.B. (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2022)
This research was conducted to determine the comfort of the vegetation based on the conditions of temperature and humidity. This research was conducted in the Nostalgia Park Green Open Space and Piet A. Tallo Street Kupang City, East Nusa Tenggara which was carried out for 1 month, from July to August 2021. This study used the path method by determining the data collection sample based on the dominant vegetation in the area and data analysis using descriptive analysis. The data is processed using the Temperature Humidity Index (THI) formula. The results showed that the comfort of the vegetation in the Green Open Space area of Taman Nostalgia and Jalan Piet A. Tallo was in moderate condition with THI values in the range of 23-27. The Green Open Space area has heterogeneous forest types with the most dominant vegetation in both areas being White Teak (Gmelina arborea) and Flamboyan (Delonix regia). This forest type allows vegetation of the same type in these two green open spaces to have different temperature and humidity data.